Evaluasi Pemanfaatan Sistem Informasi Desa (SID) di Kabupaten Gresik (Studi kasus di seluruh Desa pada Kecamatan Ujungpangkah) - Syamsi, Nur; Indarto, Tomi; Kholifah, Anik Nur; Hakim, Lutfi; Sutarto, Auditya Purwandini; Suparno, Suparno; Afiyat, Nur (Jurnal Optimalisasi, 2025)
This study aims to evaluate the utilization of the Village Information System (Sistem Informasi Desa or SID) in Gresik Regency, with a case study involving all villages in the Ujungpangkah District. The Village Information System (SID) serves as a crucial tool for enhancing the efficiency of public services at the village level and promoting transparency and accountability in village governance. However, its implementation and utilization still face various challenges. This research employs both qualitative and quantitative approaches to obtain a comprehensive overview of the extent to which SID has been implemented and utilized by the villages in Ujungpangkah District. Data were collected through in-depth interviews, questionnaires, and field observations. The analysis was conducted using descriptive and inferential methods to identify the factors influencing SID utilization, including technical aspects, human resources, and government support. The findings indicate that the utilization of SID in these villages remains suboptimal, with the main obstacles being limited technological infrastructure, lack of training for village officials, and insufficient support from the local government. The recommendations derived from this study are expected to serve as a reference for local governments in improving the utilization of SID to achieve better village governance.